Existence and asymptotic stability of continuous solutions for integral equations of product type - Mahmoud Bousselsal; Azzeddine Bellour (Journal of Innovative Applied Mathematics and Computational Sciences, 2021)
In this paper, we study the existence of a continuous solution for a nonlinear integral equation of a product type. The analysis uses the techniques of measures of noncompactness and Darbo's fixed point theorem. Our results are obtained under rather general assumptions. Moreover, the method used in the proof allows us to obtain the asymptotic stability of the solutions.